Discordance between ROTEM® clotting time and conventional tests during unfractionated heparin–based anticoagulation in intensive care patients on extracorporeal membrane oxygenation. Issue 1 (January 2016) - Prakash, S.; Wiersema, U. F.; Bihari, S.; Roxby, D.
We hypothesised that ROTEM ® (Basel, Switzerland) INTEM® (ROTEM, Basel, Switzerland) clotting time (CT) would have good agreement with activated partial thromboplastin time (aPTT) in determining whether a dose adjustment should be made to the unfractionated heparin (UFH) infusion in patients on extracorporeal membrane oxygenation. All patients treated with extracorporeal membrane oxygenation over a five-year period were included for data analysis. Retrospective analysis was performed of prospectively collected data points, wherein aPTT, activated CT and ROTEM was performed simultaneously to monitor UFH–based anticoagulation. Two hundred data points were available for analysis. Turnaround time was shortest for activated CT followed by ROTEM and aPTT. Despite achieving therapeutic aPTT targets, the majority (>50%) of INTEM CT results were within normal limits. The aPTT and INTEM CT results correlated weakly (r=0.31, 95% confidence interval [0.17, 0.43]) and there was no agreement between the directional changes of aPTT and INTEM CT results on successive days (χ2 = 2.33, P =0.17). Due to relative insensitivity, INTEM CT–guided UFH titration was estimated to result in a 289% increase in incidence of up-titration, over aPTT–guided titration. The INTEM CT results (r=0.36, 95% confidence interval [0.23, 0.48]) correlated weakly with UFH infusion rates. The UFH infusion rate only explained 13% variability in INTEM CT values. While haemorrhagic complications were frequent, no major clotting complications were encountered. Our results demonstrated that aPTT and INTEM CT do not provide equivalent information to guide UFH infusion rate titration during extracorporeal membrane oxygenation. Our study suggests caution regarding the use of ROTEM for guiding UFH–based anticoagulation as it may lead to excessive UFH exposure.